Association between liver cirrhosis and estimated glomerular filtration rates in patients with chronic HBV infection. Issue 33 (14th August 2020) - Wang, Dexin; Yan, Xiuping; Zhang, Min; Ren, Cuicui; Wang, Lili; Ma, Jiewen; Guo, Lu
Abstract : Abstract: To investigate the estimated glomerular filtration rates of chronic hepatitis B (CHB) patients with or without liver cirrhosis, and to explore the related risk factors. A total of 559 CHB patients were enrolled. Liver cirrhosis was diagnosed with ultrasound. The Child-Pugh scoring system was used to stage patients with liver cirrhosis. The Modification of Diet in Renal Disease (MDRD) formula was used to calculate the estimated glomerular filtration rate (eGFR). A total of 296 patients were involved. The results showed that the incidence of renal impairment in patients with liver cirrhosis was 8.45% (25/296). The incidence of renal impairment in Child-Pugh C patients was significantly higher than that in Child-Pugh B and Child-Pugh Grade A patients (i.e., 17.2% [17/99] vs 6.67% [7/105] vs 1.09% [1/92], respectively, P  < .001); age, hyperuricemia, and Child-Pugh score are all risk factors for impaired renal function. With the deterioration of liver function in patients with cirrhosis, the incidence of impaired renal function has increased significantly, and renal function should be closely monitored to guide patients in clinical medication.